Feasibility Assistance for Housing Project Development Progress - Veronika Nugraheni Sri Lestari; Gitta Aulia Putri Kharismanda; Chandra Kartika; Nurmawati Nurmawati (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2022)
Technological developments and monetary development request an expansion in the quality and nature of Human Resources who are solid, gifted and prepared to work. Hence, it is important to make a procedure for delivering dependable, gifted and prepared to work who can apply their insight and abilities in the field of work which at last can diminish joblessness rate in a country. Housing planning and development which is engaged in housing project development requires the feasibility of the progress of the housing project development process. This is carried out from the stage of land acquisition, construction, to housing marketing. The result of this study demonstrates that Skills in making reports or projects should be improved by going to preparing or non-formal training in the field of bookkeeping and PC applications. Then, at that point, while encountering issues in carrying out the lodging program help, we want to ask different representatives who are really understanding or more senior so the work can be finished appropriately. In helping the lodging progrees, every individual is expected to have high liability, meticulousness, exactness, trustworthiness, tolerance and reliability for every relegated undertaking and occupations, and furthermore that discipline in observing and agreeing with guidelines and time discipline is our obligation so the given errand can be finished appropriately and on schedule